2008
DOI: 10.1056/nejmoa071968
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Arrest Associated with Early Repolarization

Abstract: Among patients with a history of idiopathic ventricular fibrillation, there is an increased prevalence of early repolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
1,101
16
41

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,290 publications
(1,231 citation statements)
references
References 25 publications
51
1,101
16
41
Order By: Relevance
“…However, in addition to J‐wave augmentation, QRS interval widening and J‐ST–segment elevation were also documented in previously reported cases of ERS, in accordance with electrocardiographic characteristics observed in acute ischemia settings 9, 10, 19. In this study, available ECGs before the onset of VF in 3 patients with CAS also showed specific J‐wave and QRST characteristics, in agreement with previous ERS studies 1, 12. Inamura et al showed that the J wave was augmented in the leads associated with ischemic areas, caused by acetylcholine‐induced vasospasm 10.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, in addition to J‐wave augmentation, QRS interval widening and J‐ST–segment elevation were also documented in previously reported cases of ERS, in accordance with electrocardiographic characteristics observed in acute ischemia settings 9, 10, 19. In this study, available ECGs before the onset of VF in 3 patients with CAS also showed specific J‐wave and QRST characteristics, in agreement with previous ERS studies 1, 12. Inamura et al showed that the J wave was augmented in the leads associated with ischemic areas, caused by acetylcholine‐induced vasospasm 10.…”
Section: Discussionsupporting
confidence: 92%
“…J‐wave augmentation before the onset of VF is considered a typical electrocardiographic feature in patients with ERS 1, 12. However, in addition to J‐wave augmentation, QRS interval widening and J‐ST–segment elevation were also documented in previously reported cases of ERS, in accordance with electrocardiographic characteristics observed in acute ischemia settings 9, 10, 19.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations